Transcriptome-wide and differential expression network analyses of childhood asthma in nasal epithelium - Forno, Erick (J Allergy Clin Immunol, 2020)
In a transcription-wide association study of nasal epithelium, we identify novel and previously reported susceptibility genes for atopic asthma in children and show that gene co-expression networks differ markedly between children with and without atopic asthma.